Costa Rica : Ex Post Evaluation of Exceptional Access Under the 2009 Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2011)
This report reviews Costa Rica's performance under the Stand-By Arrangement. At the time of the global crisis, Costa Rica's macroeconomic policy framework was constraining policy options. The financial program's design was consistent with its policies and objectives. Structural reforms during the program period were slow, and fiscal risk increased. The program's design reflected the challenges and priorities that Costa Rica faced at that time, as well as policy constraints. Program conditionality focused on maintaining sufficient buffers in the form of foreign exchange reserves.